Estudo de um sistema de propulsão de veículos elétricos populares - Luczkiewicz, Claudinilson Alves (Universidade do Vale do Rio dos Sinos, 2017)
The objective of this study is to explore the alternative of electric automotive propulsion and present a proposal for the use of industrial equipment ever produced on a large scale that can be inserted to the propulsion subsystem of an electric vehicle with popular features, and thus offer an alternative fast integration of vehicles in urban centers. The power and torque characteristics of the alternative proposal were investigated for longitudinal vehicle dynamics and its equipment sold. Three driving settings are evaluated, and an electric thruster connected in a unique way, with two independent propellers connected to the rear wheels and four independent drivers directly connected to the wheels. It is also observed the characteristic of economic viability may present attractive costs to the final consumer. The main results, according to the technical characteristics of the equipment, economic viability and weight, show that the minimum power required for the performance of the traction subsystem should be 33.70 kW with energy consumption of 19.10 kWh and distributed in the configuration with two independent propellers connected to the rear wheels.
Keywords: Propulsão alternativa; Veículos elétricos populares; Equipamentos industriais em veículos elétricos; Alternative propulsion; Popular electric vehicles; Industrial equipment for electric vehicles; ACCNPQ::Engenharias::Engenharia Elétrica